ANALISIS SEBARAN DAN FAKTOR PENYEBAB KEMISKINAN DI KABUPATEN BANDUNG BARAT - Sarah Nita Hasibuan; Bambang Juanda; Sri Mulatsih (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2019)
Poverty is a level of life that below the minimum standard of living needs. The dominant factors that influence the emergence of poverty include education, income, location, limited access to health, finance and public services. Poverty is also one of the crucial issues in West Bandung Regency, where West Bandung Regency has the highest poverty rate compared to surrounding areas such as Bandung City, Bandung Regency, and Cimahi City. The purposes of this study are to analyze the pattern of spatial poverty distribution in general (Moran Index) and in each village (2) Analyze the factors that influence poverty in West Bandung Regency, which are carried out in 165 villages. The results of this study state that there was a positive spatial autocorrelation of 0,464173 which indicated the existence of a link between the poor population in each village and the pattern of poverty that clustered. The LISA test showed the poverty level of the population was clustered into four poverty clusters, namely 17 villages that were in the high-high criteria, 31 villages in the low-low criteria, 5 villages in the low-high criteria and 1 village in the high-low criteria . The factors that influenced poverty in West Bandung Regency were population, education level, village fund allocation, number of groceries, and village funds, while the village index builds, the distance of villages to the capital and the number of people using National electrical corporate (PLN) were not significant to reduce poverty.